Social Network Analysis Pergerakan Ternak Babi Terhadap Penyebaran Penyakit Classical Swine Fever atau Hog cholera di Kabupaten Sikka Pulau Flores Provinsi Nusa Tenggara Timor, Indonesia - Petrus Malo Bulu; Ewaldus Wera; Margaretha Sikko (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
Classical Swine Fever (CSF) is a serious and highly infectious viral disease of both domestic pigs and wild boar. The disease was classified as a pestivirus within the family Flaviviridae that forms a group of economically important pathogens. This disease has become endemic in some districts in Nusa Tenggara Timur. However, it gained entry into the district of Sikka in 2016. This disease was suspected to gain entry into Sikka by the movements of pigs (pig trading). However, it was not certain how this disease introduced and transmitted into the region. This research was aimed to identify and analyze the movement of pigs through the trade chain as a pathway to spread the disease within farms in the district of Sikka. A total of 57 respondents were interviewed in this study involved sellers and buyers in the markets (4 buyers and 4 sellers in each market-a total of 32 people), suppliers of pigs (10 people), and pig farmers as many as 5 respondents per village (3 villages selected purposively). A face-to-face interview was conducted to obtain information from the respondents. The results of the study found that market sellers and buyers are actively moving through the market network, and therefore could potentially contribute to the spread of CSF in Sikka, if an outbreak occurred in the region. The in and out-degree values in the current study suggest that pigs were moving in and out of the areas through the movement of sellers and buyers. This study also found that Node S5 plays a key role in transmitting information to all other nodes in the network of pigs in Sikka. This study also found that there was potential movement of pigs in different villages in Sikka through the directed links or ties, which could contribute to the transmission and spread of CSF.